FISH FROM THE PINTUYACU STREAM, ITAYA RIVER BASIN, PERUVIAN AMAZON - RUIZ TAFUR, Kevin Morgan (2024)
The present work corresponds to a fish inventory, carried out between August and September 2019, in three sampling sites in the Pintuyacu stream, a tributary of the Itaya River basin, in the Peruvian Amazon. Based on 504 individuals analyzed, 117 species were identified, corresponding to 33 families and 8 orders. The most diverse order was Characiformes (65 species, 55.6%), followed by Siluriformes (31 species, 26.5%). At the Characidae family level, it presents the highest species richness with 24 species (20.5%). The most abundant species were Stethaprion erythrops (13.1%, 66 individuals), Knodus smithi (13.1%, 66 individuals) and Bujurquina peregrinabunda (6.2%, 31 individuals). Species for ornamental and consumer use were recorded. No threatened species were recorded and most were classified as Least Concern (LC), according to IUCN criteria. The present study is the first to present a list of the ichthyofauna present in the Pintuyacu stream and consequently the first inventory published for the Itaya River basin. Which highlights the need to continue carrying out ichthyological inventories, with the aim of enriching the knowledge of the freshwater ichthyofauna of the country and the Amazon region, as well as applying necessary measures for the conservation of our ichthyological resources.